Social status and egalitarianism in non-lineage-based, agrarian communities in sub-Saharan Africa: An analysis of funeral attendance - Abigail Barr; Mattea Stein (The University of Nottingham, Centre for Research in Economic Development and International Trade (CREDIT), 2022)
This paper explores the role of social status in relationships between rich and poor in non-lineage-based, agrarian communities by analysing who goes to whose funerals in six resettled Zimbabwean villages. Funerals allow social status to be observed because non-attendance is a sign of disrespect. We find that the richer a household hosting a funeral, the less likely heads of neighbouring households are to attend. This is consistent with the existence of an egalitarian norm that is being violated, to some degree, by the richer households. This norm is stronger among kin but also holds for non-kin. An analysis of assistance provision offers no evidence that some richer households comply with the norm and eschew punishment. While the egalitarian norm appears weak (punishment for norm violation is exerted but compliance does not follow), patron-client relationships appear not to have emerged in its place.
Keywords: O15; O17; Z19; I39; 330; Social status; Egalitarian norms; Patronage; Sub-Saharan Africa; Funeral attendance